Analisis Dampak Pencemaran Sampah Plastik Terhadap Populasi Ikan Dan Kualitas Lingkungan Di Wilayah Muara - Asokhiwa Zega (CV. SINAR HOWUHOWU, 2026)
Plastic waste pollution has become one of the most serious environmental threats to aquatic ecosystems, particularly in estuarine areas that serve as critical habitats for various fish species. This study aimed to analyze the impact of plastic waste pollution on fish populations and environmental quality in estuarine ecosystems. A quantitative descriptive approach with field survey methods was employed. Data collected included plastic waste concentrations in water and sediments, microplastic content in fish bodies, water quality parameters, and fish population structure. Ecological indices, Pearson correlation analysis, and linear regression were used to determine the relationship between plastic pollution levels and fish population dynamics. The results revealed that estuarine areas with high plastic concentrations exhibited greater microplastic accumulation in fish, lower water quality, and reduced fish diversity. Approximately 68% of the examined fish contained microplastics in their digestive tracts, with an average of 2.4 ± 0.8 particles per individual. Pearson correlation analysis indicated a strong negative relationship between plastic concentration and fish diversity index (r = −0.82; p < 0.05). Furthermore, plastic pollution caused physiological disturbances in fish and contributed to a decline in fishery catches reported by local fishermen. These findings demonstrate that plastic waste pollution has significant impacts on estuarine ecosystem health and the sustainability of fishery resources. Therefore, integrated and ecosystem-based plastic waste management strategies are urgently needed to maintain environmental quality and conserve fish populations in estuarine regions.